Expression of particulate methane monooxygenase (pMMO) proteins in plants for methane detoxification - Spatola Rossi, T (2022)
Methane is a potent greenhouse gas which has contributed to approximately a fifth of global warming since pre-industrial times and its concentration continues to rise yearly in parallel to that of CO2. Anthropogenic activities contribute to 70% of global emissions, with the main sources being the extraction and transport of fossil fuels, farming of livestock, waste management, rice agriculture, and biomass burning. Rice cultivation is a major source of anthropogenic emissions due to the flooded conditions of the soil and presence of organic matter which pose favourable conditions for biotic methanogenesis. In turn, the rice plants transport the greenhouse gas into the atmosphere through the porous aerenchyma tissue in a process termed “the chimney effect”. Strategies for mitigating rice emissions include modifying the watering regimes and the supplementation of organic additives. However, these practices are not always feasible for farmers and may introduce drawbacks such as lower grain yields and the emission of N2O. In this thesis, the bioengineering of rice for methane mitigation is postulated. In nature, methanotroph bacteria use methane as their source of carbon and energy via methane monooxygenase enzymes (MMOs), and predominantly through particulate methane monooxygenase (pMMO). pMMO is encoded in an operon and forms a membrane-bound nonamer complex composed of three different protein subunits. The heterologous expression of pMMO has been deemed challenging due to its membrane localization and copper content. In this work the recombinant expression of pMMO in tobacco and Arabidopsis is presented as a proof of concept, with the further aim of bioengineering rice to contain pMMO and reduce emissions from paddy fields. The pmoC, pmoA and pmoB subunits were targeted to the endoplasmic reticulum (ER) individually, and gene stacking strategies were explored. The use of 2A self-cleaving peptides resulted in a successful gene stacking methodology to express all the subunits in the ER. The 2A pMMO polypeptide expression was greatly enhanced by co-expression with P19, and did not induce major disruption or modification to ER structure and dynamics. This thesis shows, for the first time, that the pMMO proteins can be co-expressed in plant cells without apparent detrimental effects, and strategies for obtaining a functional enzyme in the recombinant system are investigated and discussed.